(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Drozdova I. P. Seminars and workshops for development of creative abilities of Students of non-philological profile concerning professional communication on specialty. The paper analyzes the specifics of seminars and workshops with the aim of developing creative skills of students concerning professional communication on specialty is determined, and examples of models of seminars and workshops as effective organizational forms of work in high school are offered.